Reality in the Work of Publius Ovidius Naso as a Manifestation of the Mutation of a Change of Sense - Sierny, Tadeusz (Folia Philosophica, 2000)
The article contains reflections concerning the zones of thymos and fronesis in Ovid’s oeuvre. To carry out an analysis of those two zones is necessary to show that they exemplify the process, and eventually also the effect which J. Banka calls ,.the mutation of a change of sense”. This type of mutation leads to a change of the real ontology into a virtual one. Owing to our analysis of this kind of transformation we arrive at a new understanding of Ovid’s work, we reveal its transcendental and metaphysical nature. The purpose of publishing this study was to present an attempt at a practical application of this kind of methodology.